2012
DOI: 10.1111/j.1365-2575.2012.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding customers' repeat purchase intentions in B2C e‐commerce: the roles of utilitarian value, hedonic value and perceived risk

Abstract: Customer loyalty or repeat purchasing is critical for the survival and success of any store. By focusing on online stores, this study investigates the repeat purchase intention of experienced online buyers based on means‐end chain theory and prospect theory. In the research model, both utilitarian value and hedonic value are hypothesised to affect repeat purchase intention positively. Perceived risk is hypothesised to affect repeat purchase intention negatively and moderate the effects of utilitarian and hedon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
699
6
70

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 992 publications
(920 citation statements)
references
References 106 publications
52
699
6
70
Order By: Relevance
“…In this context, it would be of interest for research and business alike, how older user groups such as silver surfers may be engaged in social commerce as mentioned by Brock et al (2011). According to Chiu et al (2014), utilitarian and hedonic values have direct effects on repeat purchase behavior. Thereof, more research needs to be done to further investigate the relative importance of hedonic and utilitarian value components and their interplay in a social commerce setting.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, it would be of interest for research and business alike, how older user groups such as silver surfers may be engaged in social commerce as mentioned by Brock et al (2011). According to Chiu et al (2014), utilitarian and hedonic values have direct effects on repeat purchase behavior. Thereof, more research needs to be done to further investigate the relative importance of hedonic and utilitarian value components and their interplay in a social commerce setting.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…In contrast, Scholz et al (2013) have found that actually Bneutral^content shared by users of an online community positively affect the conversion rate of online shop visitors. Finally, some contributions in the field of user behavior investigate factors influencing customer loyalty towards social shopping, social networking, or social gaming websites in terms of repeat purchase behavior (e.g., Chiu et al 2014;Goel et al 2013;Jang et al 2008;Zhou et al 2014). Chiu et al (2014), for instance, explore repeat purchase intention of experienced online buyers.…”
Section: Research Theme: User Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Close and Kukar-Kinney (2010) have reported that the same two motivations, in the form of informative and entertainment values, will act as antecedents of purchase intentions. Similarly, Chiu et al (2012) have studied customers' experiences and posit that both utilitarian and hedonic values positively affect future purchase intentions.…”
Section: The Role Of Emotions On Formulating Shopping Behaviorsmentioning
confidence: 99%
“…Some researchers have work on utilitarian and hedonic motivations for shopping offline in traditional brick and mortar retail store (Babin et al, 1994;Childers et al 2001;Hirschman and Holbrook, 1982;Ertekin, 2014;Irani and Hanzaee, 2011;Arnold and Reynolds, 2012;Roy Dholakia, 1999;Ottar Olsen and Skallerud, 2011;) and some studied by considering online retail context (Davis et al, 2014;Martínez-López et al, 2014;Chang, andChen, 2015,Childers et al, 2001;Bhat-nagar and Ghose, 2004;Van Slyke et al, 2002;Kim, 2006;To et al, 2007;Bridges and Florsheim, 2008;Chiu et al, 2014;). The main purpose of all these studies is to understand "Why people shop?"…”
Section: Related Review Of Literaturementioning
confidence: 99%